Pengaruh Sikap Patuh Hukum, Sikap terhadap Legalitas Pembelian, dan Kinerja Produk terhadap Minat untuk Membeli CD Bajakan Bermerek - Yazid, Muchsin Muthohar (Sinergi: Kajian Bisnis dan Manajemen, 2008)
‘The reasoned-action theory’ states that consumer behavior may reflex either individual attitude towards behavior and individual behavior concerning subjective norms. This research is aim to identify the influence of law conformity, attitude towards purchase legality, and the performance of pirated compact disk (CD) product on the consumers’ intention to buy pirated-branded CD. As many as 500 respondents were taken from five universities in Yogyakarta by quota-convenience sampling method. Regression analysis shows that those three variables simultaneously affect the dependent variables. Its individual affect, however, is different. Law conformity, and attitude towards purchase legality do not affect the dependent variable, meanwhile the performance of CD affect it. Paying attention on the level consumption status of responden, it is found that price and availabity of CD is more important than prestige. In addition, demographic analysis shows that consumption status, group, tradition, and religion do not affect the motivation on purcahsing CD.Keywords: behavior, attitude, subjective norm, pirated-branded CD